Assessment and Implementation Plan of Knowledge Management at PT LAPI Divusi - Irvayanti, Rian; Tjakraatmadja, Jann Hidajat (The Indonesian Journal of Business Administration, 2014)
Abstract- PT. LAPI Divusi is an IT consultant that has been founded for 10 years. During 10 years LAPI Divusi have gain many experience and knowledge. Since founded at 2004, LAPI Divusi has low engagement of their employee. Employee normally will stay in company for two until four years (especially for engineer). Employee turnover since 2009 to 2013 are 28.4%. When employees leave the company, they would bring their knowledge and experience. If company couldnâ€™t capture the knowledge, company will lose it. This condition will lead to large loss for company. High operational cost can not be avoided, one of the causes was duplicate work / reinventing the wheel and employee need extra time to learn and get information. Aware this situation, company attempt to implement knowledge management since 2008, but still didn't success. With assessment of KM readiness using APO KM Framework, strength and opportunity for improvement will be gained to implement knowledge management in PT. LAPI Divusi.Keyword: IT Consultant,Â  Knowledge Management, KM readiness, assessment